Productivity of Homogeneous and Heterogeneous Oat Populations at Two Sowing Dates - Md Khairuddin, Narimah (1991)
Eight spring oat (Avena sativa L.) lines differing in height and maturity were categorized into three groups. Group I contained lines variable in height and maturity, whereas Groups II and III were variable in maturity and height, respectively. The lines in each group were grown in pure lines and in blends at two sowing dates, to study the effect of different sowing dates on homogeneous and heterogeneous oat populations. The traits measured were vegetative growth rate, reproductive growth rate, and grain yield. The means of homogeneous lines and heterogeneous oat populations performed equally in both growth rate and grain yield. The grain yields of the blends were within the range of their component pure lines and the blends did not show any advantage at the late sowing date.